Hypoxic-Ischemic Injury in the Developing Brain: The Role of Reactive Oxygen Species Originating in Mitochondria - Vadim S. Ten; Anatoly Starkov (Neurology Research International)
Mitochondrial dysfunction is the most fundamental mechanism of cell damage in cerebral hypoxia-ischemia and reperfusion. Mitochondrial respiratory chain (MRC) is increasingly recognized as a source for reactive oxygen species (ROS) in the postischemic tissue. Potentially, ROS originating in MRC can contribute to the reperfusion-driven oxidative stress, promoting mitochondrial membrane permeabilization. The loss of mitochondrial membranes integrity during reperfusion is considered as the major mechanism of secondary energy failure. This paper focuses on current data that support a pathogenic role of ROS originating from mitochondrial respiratory chain in the promotion of secondary energy failure and proposes potential therapeutic strategy against reperfusion-driven oxidative stress following hypoxia-ischemia-reperfusion injury of the developing brain.